Synthesis and Characterization of Unsaturated Succinic Acid Biobased Polyester Resins - Lazaros Papadopoulos; Lamprini Malletzidou; Dimitra Patsiaoura; Andreas Magaziotis; Eleni Psochia; Zoi Terzopoulou; Konstantinos Chrissafis; Charles Markessini; Electra Papadopoulou; Dimitrios N. Bikiaris (Applied Sciences, 2021)
Polymers from renewable feedstocks are receiving increasing attention as the awareness about environmental issues derived from petroleum exploitation and waste accumulation is growing. With unsaturated polyester resins being one of the most used classes of polymers worldwide, the utilization of biobased monomers for manufacturing is more relevant than ever. In the present work, succinic acid, one of the most promising biobased building blocks, was incorporated in the structure of the resins in question to increase their biobased content. By reacting with ethylene glycol (EG) or poly(ethylene glycol) and maleic anhydride (MA) at several molar rations, unsaturated polyester resins (UPRs) were prepared. Their synthesis was evaluated by a variety of spectroscopical techniques, and their rheological properties made use of the reactive diluent mandatory for facilitating processing. Thus, in a second stage acrylic acid (AA) was used as cross-linking agent in the present of initiators and accelerators producing thermosetting resins. Differential scanning calorimetry (DSC) was employed to screen the cross-linking procedure, whereas with X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared spectroscopy (FTIR) it was proven that thermosetting resins were prepared. The thermal stability of the cured materials was evaluated by thermogravimetric analysis (TGA).